2021
DOI: 10.1101/2021.02.10.430684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZC3H4 restricts non-coding transcription in human cells

Abstract: The human genome encodes thousands of non-coding RNAs. Many of these terminate early and are then rapidly degraded, but how their transcription is restricted is poorly understood. In a screen for protein-coding gene termination factors, we identified ZC3H4. However, its depletion causes upregulation and extension of hundreds of unstable transcripts, particularly antisense RNAs and those transcribed from so-called super-enhancers. These loci are occupied by ZC3H4, suggesting that it directly functions in their … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Although many antisense transcripts contain multiple AAUAAA sequences, most still terminate RBBP6-independently (Supplementary Figures 1B and C). Similarly, we recently showed that the PAS-dependent 5'3' exonucleolytic torpedo terminator, XRN2, does not affect antisense transcriptional termination 9 . Therefore, although some antisense transcripts are polyadenylated, most antisense transcription can terminate using PAS-independent mechanisms.…”
Section: Polyadenylation Factor Depletion Does Not Increase or Extend...mentioning
confidence: 79%
See 4 more Smart Citations
“…Although many antisense transcripts contain multiple AAUAAA sequences, most still terminate RBBP6-independently (Supplementary Figures 1B and C). Similarly, we recently showed that the PAS-dependent 5'3' exonucleolytic torpedo terminator, XRN2, does not affect antisense transcriptional termination 9 . Therefore, although some antisense transcripts are polyadenylated, most antisense transcription can terminate using PAS-independent mechanisms.…”
Section: Polyadenylation Factor Depletion Does Not Increase or Extend...mentioning
confidence: 79%
“…Reciprocally, promoter-proximal transcription from lowly expressed protein-coding transcription is INTS11-sensitive, which could reflect low CDK9 activity at those loci. We and others recently described the Restrictor complex as restraining antisense transcription 9,44,45 . Unlike Integrator, which associates with NELF-bound RNAPII 36 , Restrictor is proximal to the distinct PAF-bound RNAPII 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations